A kind of high-adhesion wear-resistant metal water-based paint and preparation method thereof

The use of a modified auxetic molecule filler in metallic water-based paints addresses wear resistance and adhesion issues by maintaining strong connections between resin molecules and fillers, enhancing the coating's mechanical properties.

CN118725668BActive Publication Date: 2024-12-13SHANGQIU BROAD CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410942892.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2024-12-13
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Existing metallic water-based paints face issues with wear resistance and adhesion due to the loss of resin molecules under high-pressure friction, leading to separation of high-hardness fillers and reduced mechanical properties.

Method used

A modified auxetic molecule is used as a filler, prepared by coupling a high-hardness composite filler with a silane coupling agent and an elastomeric polymer, with specific pH adjustments to enhance bonding and resistance.

Benefits of technology

The modified auxetic molecule enhances the adhesion and wear resistance of the coating by maintaining strong connections between resin molecules and fillers, even under friction, resulting in improved interfacial bonding and resistance to wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725668B_ABST
    Figure CN118725668B_ABST
Patent Text Reader

Abstract

The present application relates to the field of water-based coatings, specifically to a high-adhesion and wear-resistant metal water-based coating and its preparation method, which solves the problem that the resin molecules in the coating lose too many resin molecules under high-pressure friction, resulting in the high-hardness filler being detached by impact, resulting in insufficient wear resistance and adhesion of the coating; wherein the metal water-based coating uses modified extrude molecules as fillers, mixes high-hardness composite fillers with silane coupling agents to obtain coupled composite fillers, pre-treats and activates the extrude polymer, and prepares a suspension of the coupled composite filler, wherein the dispersion medium is isopropanol, and the pH is adjusted to alkaline; S4, dissolves the washed extrude polymer in an organic solvent, and adjusts the pH to acidic; S5, slowly drips the organic solution containing the extrude polymer into the suspension of the coupled composite filler, and adjusts the pH to neutral or slightly alkaline. The coating of the present application has high adhesion and stronger wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of water-based coatings, and in particular to a high-adhesion and wear-resistant metal water-based coating and a preparation method thereof. Background Art

[0002] Metallic water-based paint uses water as a solvent, and the water content of the finished product is between 15-50%, with very little volatility, and basically no toxic substances such as formaldehyde, benzene, and free TDI, which will not pollute the environment. In addition to the solvent water, water-based paints mostly use water-based resins, pigments, and other additives. All media that use water as a solvent for dispersion are water-based paints, which are further divided into silicone water-based paints, acrylic water-based paints, water-based polyurethane water-based paints, water-based epoxy resin paints, and inorganic water-based paints. Metallic water-based paints are additionally added with metallic pigments or pigments with metallic effects, giving the coating a metallic luster and texture, and relevant additives have been used to improve the shortcomings of water-based paints in terms of weather resistance, corrosion resistance, and insufficient mechanical properties.

[0003] Adding a single metal component to water-based paint will reduce the leveling property. The metal component will react with other components in the water-based paint to form agglomerates, which will affect the stability and storage life of the paint. Since the metal surface has no connection points with the polar groups in the water-based paint, it cannot be stably and uniformly dispersed in the water-based paint, which often leads to problems such as precipitation and agglomeration. In the prior art, titanate or other types of coupling agents are used to modify the surface of particles with high hardness metal as fillers. After the prepared coating is formed into a film, the mechanical properties of the coating are greatly improved. In terms of improving the wear resistance of the coating, the prior art uses a material with higher hardness as the filler to resist the impact of wear and reduce the loss of the coating, and the high hardness material is cross-linked with a modification method to couple it between the resin molecules, thereby obtaining better wear resistance.

[0004] The problem with the above method is that when using high-hardness filler to modify the connection to increase wear resistance, the resin and filler are subjected to continuous lateral friction under high pressure, which will cause the loss of resin material molecules around the high-hardness filler. After a certain amount of resin is worn away, the connection between the high-hardness filler and the resin molecules becomes weak, causing the high-hardness filler to roll and peel off, thereby greatly reducing its wear resistance.

[0005] The adhesion and wear resistance brought about by simple modification and high-hardness fillers have certain limitations. Therefore, a preparation method of a metallic water-based coating is needed to improve the wear resistance of the coating to solve the above problems. Summary of the invention

[0006] In order to solve the problem that under high-pressure friction, the resin molecules in the coating lose too much and the connection between the resin molecules and the high-hardness material becomes weak, resulting in the loss and separation of the high-hardness filler, resulting in insufficient wear resistance and adhesion of the coating, the present application provides a method for preparing a high-adhesion and wear-resistant metallic water-based coating, the filler used in the metallic water-based coating is a modified auxetic molecule, and the preparation steps of the modified auxetic molecule are as follows:

[0007] S1, mixing a high-hardness composite filler with a silane coupling agent, and performing a shaking treatment to obtain a coupled composite filler;

[0008] S2, pre-treating and activating the flexibilizing polymer, dispersing the flexibilizing polymer with an organic solution of lithium chloride, heating and washing;

[0009] S3, preparing a suspension of the coupled composite filler, using isopropanol as the dispersion medium, and adjusting the pH to alkaline;

[0010] S4, dissolving the washed flexibilizing polymer in S2 in an organic solvent, and adjusting the pH to be acidic;

[0011] S5. Slowly drop an organic solution containing an auxetic polymer into the suspension of the coupled composite filler, and adjust the pH to neutral or slightly alkaline, wherein the mass ratio of the auxetic polymer to the coupled composite filler is 1:3-6.

[0012] The present application prepares the above-mentioned filler by first performing coupling modification on the particle surface of the high-hardness composite filler so that the particle surface carries a modified group, and the high-hardness particles can be strongly connected with the elastomeric polymer. Then, the elastomeric polymer material is used. The elastomeric polymer contains an amide group, and the coupling group and the amide group can be connected to form a strong bond. The use of lithium chloride will expose the carbonyl group, which will then couple the group of the high-hardness composite filler.

[0013] Use isopropanol to disperse the coupling compound filler to prevent the generation of more active hydroxyl groups, and adjust the pH to alkaline to inhibit the coupling effect of the coupling agent, weaken the coupling group and prevent excessive coupling. The coupling agent is most active in a neutral and slightly alkaline environment, so its activity is inhibited after adjusting the pH value to facilitate the retention of active sites.

[0014] Then, the auxetic polymer material is dispersed in an organic solvent. The auxetic polymer material has carboxyl groups and amide groups at the connection site. By adjusting the pH to acidity, it is not only conducive to the existence of the carboxyl group, but also, in the subsequent addition to the suspension of the alkaline coupling composite filler, a neutralization reaction is carried out, so that the average pH tends to be neutral, which is conducive to the connection of the coupling group. The gradually activated hydroxyl groups on the coupling group are conducive to connecting with the amide groups on the auxetic polymer in the microenvironment after the pH is adjusted, and finally the high-hardness composite filler is connected with the auxetic polymer material. After the connection, filtering, precipitation and washing are carried out to obtain the final modified auxetic molecule.

[0015] When the pressure causes the stretched fibers to shrink longitudinally, the corresponding vertical surfaces of the fibers will tighten laterally, which will cause the coating to produce a greater reverse resistance force when it is pulled laterally. The coating surface will be tighter and will not shrink. The shrunk resin polymer will also expose the high-hardness particles. The physical condensation effect brought by graphite enhances the adhesion between the coating and the substrate, and also enhances the connection between the resin molecules and the tensile polymer, effectively enhancing the interfacial bonding force.

[0016] Preferably, the metallic water-based paint further comprises the following specific ingredients by weight:

[0017] Base material: 35-50 parts of water-based acrylic resin, 8-15 parts of filler, 14-18 parts of water, 8-10 parts of pigment, 0.2-0.4 parts of leveling agent, 0.2-0.4 parts of dispersant, 0.2-0.4 parts of mildew inhibitor, 0.2-0.4 parts of preservative, 0.1-0.4 parts of defoaming agent, 0.1-0.4 parts of wetting agent, 4-6 parts of isopropyl alcohol, 4-8 parts of propylene glycol butyl ether, and 5-12 parts of curing agent.

[0018] Preferably, the auxetic polymer in S2 is a linear aromatic amide auxetic polymer, and the linear aromatic amide auxetic polymer is obtained by polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl ester and p-phenylenediamine.

[0019] The above-mentioned flexographic polymer forms a molecular chain through a condensation reaction between the two carboxyl groups of 2,6-dichloroformyltetraphenylethylenediamine and the two amino groups of p-phenylenediamine, and the two adjacent 2,6-dichloroformyltetraphenylethylenediamines are oriented in opposite directions on the molecular chain, so that the p-phenylenediamine between the two 2,6-dichloroformyltetraphenylethylenediamines is connected in an inclined posture. Therefore, it has a negative Poisson's ratio on the entire polymer molecular chain, that is, the main chain of the molecule is stretched, so that the benzene rings and carboxyl groups in the vertical direction of the molecular chain extend outward, and when the main chain of the molecule shrinks, the benzene rings and carboxyl groups in the vertical direction of the molecular chain will shrink, and multiple polymer molecular chains form a honeycomb structure through hydrogen bonds.

[0020] Preferably, the high hardness composite filler is obtained by mixing a high hardness material and flaky graphite in a ratio of 1:1-3:1.

[0021] The filler is compounded with flaky graphite, which can be attracted by its van der Waals force, making it easier for the expanded polymer to condense and embed between the coatings. The flaky graphite acts as a bridge in the coating, enhancing the connectivity and cohesion within the coating. When subjected to friction and impact, it helps to reduce the formation of depressions and cracks in the coating, thereby improving the adhesion of the coating.

[0022] Preferably, the high-hardness material is one of tungsten carbide, aluminum-lithium alloy, titanium-aluminum alloy, nickel-titanium alloy, niobium-titanium alloy, tungsten steel or chrome steel.

[0023] Preferably, the particle size of the high hardness composite filler is between 30-100 μm.

[0024] Preferably, the organic solvent in step S4 is one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) or ethylene glycol dimethyl ether (EDG).

[0025] The present application further provides a high-adhesion and wear-resistant metallic water-based coating based on the above-mentioned preparation method, which is prepared by any of the above-mentioned preparation methods of the high-adhesion and wear-resistant metallic water-based coating.

[0026] Preferably, the coating thickness of the metallic water-based paint is 3 to 5 μm; the coating is baked twice, the first baking temperature is 50 to 80° C., the time is 10 to 15 minutes, and the second baking temperature is 130 to 170° C., the time is 20 to 40 minutes.

[0027] The high-adhesion and wear-resistant metallic water-based paint of the present application can also be used for coating the surfaces of automobiles, mechanical parts and metal equipment.

[0028] The beneficial effects of this application are:

[0029] 1. After the flexibilizing polymer and the high-hardness composite filler are firmly connected, an insert is formed in the metallic water-based coating. When the coating is subjected to friction, the pressure and stretching generated will cause the high-hardness composite filler to be squeezed, pulled and displaced. The flexibilizing polymer is also subjected to the same squeezing. When the flexibilizing polymer material is stretched along the molecular chain, the stretching of the vertical molecular chain is also generated, thereby exerting a force on the high-hardness composite filler coupled to the side chain of the flexibilizing polymer, so that the high-hardness composite filler will be subjected to the force of the organic molecular chain, and the "high-hardness composite filler" will bulge outward to resist friction, reduce the wear of the resin and other polymer coatings, and be more wear-resistant.

[0030] 2. When dispersing the coupled composite filler, the present application uses isopropyl alcohol, which will not cause excessive hydrolysis of the coupling groups and will not produce too many active hydroxyl groups, so that the coupled composite filler will not agglomerate at one end of a single flexibilizing polymer material due to excessive activation groups, thereby making the paint film have better continuity and connection strength in the subsequent coating film formation process.

[0031] 3. Another improvement of the present application is that by adjusting the pH in the suspension of the coupling composite filler to alkaline and adjusting the organic solution of the flexibilizing polymer to an acidic environment, on the one hand, the activity of the coupling group of the coupling agent is suppressed to prevent excessive cross-linking, and on the other hand, the carboxyl group on the side chain of the flexibilizing polymer is protected. Then, in the subsequent mixing process, the flexibilizing polymer is evenly coupled with the coupling composite filler by dropwise addition, and the activity of the coupling group is improved during the acid-base neutralization process, thereby enhancing the coupling effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the auxetic polymer molecule of the present application.

[0033] Figure 2 Schematic diagram of adhesion and g weight of adhered material in Table 1 of this application. DETAILED DESCRIPTION

[0034] The following will refer to the attached Figure 1 and attached Figure 2 The embodiments of the present application are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present application and are not intended to limit the protection scope of the present application.

[0035] The specific types of materials used in this embodiment are as follows:

[0036] Pigments: Phthalocyanine Blue BGS, BASF D5800, Pigment Red 254, Pigment Red 122, Permanent Red F3RK, Permanent Red F5RK.

[0037] Leveling agent: BYK-333

[0038] Dispersant: B6211

[0039] Antifungal agent: C-128

[0040] Preservative: RC-50

[0041] Defoamer: F-111 Defoamer

[0042] Wetting agent: Momentive CoatOsil 77

[0043] Curing agent: Desmodur N 3390

[0044] Preparation Example 1

[0045] Preparation of modified auxetic molecules

[0046] S1. Take 20g of aluminum-lithium alloy particles with a particle size of 50-70μm and 10g of flaky graphite with a sheet diameter of 50μm and a thickness of 300nm, weigh and compound them using an analytical balance, use a measuring cylinder to quantitatively prepare enough silane coupling agent KH560 with a mass fraction of 10%, and use ethanol as the solvent. Mix the above-prepared aluminum-lithium alloy-graphite with the prepared silane coupling agent, shake it with an oscillator for 5min, react for 1.5h, filter and dry to obtain a coupled composite filler.

[0047] S2. The linear aromatic amide flexographic polymer obtained by the polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl ester and p-phenylenediamine is subjected to ultrasonic impurity removal treatment. After drying, 6 g of the flexographic polymer is irradiated with ultraviolet light for 60 minutes, and then irradiated for 3 minutes under vacuum conditions using a YAMATO PR501-A low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W. The gas medium is one of N2. Ethanol is used as a dispersing solvent, and a lithium chloride anhydrous ethanol solution with a mass fraction of 6% is prepared. The treated linear aromatic amide flexographic polymer is immersed in the lithium chloride anhydrous ethanol solution, the temperature is raised to 70°C, the treatment time is 1.5 hours, and the activated flexographic polymer is obtained after washing with clean water and drying.

[0048] S3, immersing the coupled composite filler in isopropanol, stirring with an external stirrer to form a suspension, and adjusting the pH to 10.0 with a sodium hydroxide solution having a concentration of 0.1 mol / L;

[0049] S4, dissolving the activated auxetic polymer material obtained in S2 in a dimethyl sulfoxide solution, and adjusting the pH to 3.0;

[0050] S5. Add the dimethyl sulfoxide solution containing the activated auxetic polymer to the suspension of the coupled composite filler by dropwise addition at a rate of 80 ml / min. React for 4 h, take out the modified auxetic molecules, wash them alternately with deionized water and ethanol, and dry them for later use.

[0051] Preparation Example 2

[0052] Preparation of modified auxetic molecules

[0053] S1. Take 30g of tungsten carbide particles with a particle size of 70-100μm and 10g of flaky graphite with a sheet diameter of 70μm and a thickness of 500nm, weigh and compound them using an analytical balance, use a measuring cylinder to quantitatively configure enough silane coupling agent KH560 with a mass fraction of 10%, and use ethanol as the solvent. Mix the above-prepared aluminum-lithium alloy-graphite with the prepared silane coupling agent, shake it with an oscillator for 5min, react for 2h, filter and dry, and obtain a coupled composite filler.

[0054] S2. The linear aromatic amide flexographic polymer obtained by the polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl ester and p-phenylenediamine is subjected to ultrasonic impurity removal treatment. After drying, 12g of the flexographic polymer is irradiated with ultraviolet light for 120 minutes, and then irradiated for 3 minutes under vacuum conditions using a YAMATO PR501-A low-temperature plasma treatment device with a radio frequency of 13.56MHz and an output power of 300W. The gas medium is one of H2; ethanol is used as a dispersing solvent, and a lithium chloride anhydrous ethanol solution with a mass fraction of 8% is prepared. The treated linear aromatic amide flexographic polymer is immersed in the lithium chloride anhydrous ethanol solution, the temperature is raised to 85°C, the treatment time is 2h, and the activated flexographic polymer is obtained after washing with clean water and drying.

[0055] S3, immersing the coupled composite filler in isopropanol, stirring with an external stirrer to form a suspension, and adjusting the pH to 11.0 with a sodium hydroxide solution having a concentration of 0.1 mol / L;

[0056] S4, dissolving the activated flexibilizing polymer material obtained in S2 in N,N-dimethylformamide solution, and adjusting the pH to 4.0;

[0057] S5. Add the N,N-dimethylformamide solution containing the activated auxetic polymer to the suspension of the coupled composite filler by dropping at a dropping speed of 100 ml / min. React for 4 hours, take out the modified auxetic molecules, wash them alternately with deionized water and ethanol, and dry them for use.

[0058] Preparation Example 3

[0059] Preparation of modified auxetic molecules

[0060] S1. Take 10g of niobium-titanium alloy particles with a particle size of 30-50μm and 10g of flaky graphite with a sheet diameter of 30μm and a thickness of 200nm, weigh and compound them using an analytical balance, use a measuring cylinder to quantitatively prepare enough silane coupling agent KH560 with a mass fraction of 10%, and use ethanol as the solvent. Mix the above-prepared aluminum-lithium alloy-graphite with the prepared silane coupling agent, shake it with an oscillator for 5min, react for 1h, filter and dry to obtain a coupled composite filler.

[0061] S2. The linear aromatic amide elastomeric polymer obtained by the polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl ester and p-phenylenediamine is subjected to ultrasonic impurity removal treatment. After drying, 3.5 g of the elastomeric polymer is irradiated with ultraviolet light for 40 minutes, and then irradiated for 2 minutes under vacuum conditions using a YAMATO PR501-A low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W. The gas medium is one of NH3; ethanol is used as a dispersing solvent, and a lithium chloride anhydrous ethanol solution with a mass fraction of 5% is prepared. The treated linear aromatic amide elastomeric polymer is immersed in the lithium chloride anhydrous ethanol solution, the temperature is raised to 60°C, the treatment time is 1 hour, and the activated elastomeric polymer is obtained after washing with clean water and drying.

[0062] S3, immersing the coupled composite filler in isopropanol, stirring with an external stirrer to form a suspension, and adjusting the pH to 9.0 with a 0.1 mol / L sodium hydroxide solution;

[0063] S4, dissolving the activated auxetic polymer material obtained in S2 in ethylene glycol dimethyl ether solution, and adjusting the pH to 2.0;

[0064] S5. Add the ethylene glycol dimethyl ether solution containing the activated auxetic polymer to the suspension of the coupled composite filler by dropwise addition at a rate of 50 ml / min. React for 4 h, take out the modified auxetic molecules, wash them alternately with deionized water and ethanol, and dry them for later use.

[0065] The high-hardness material in the above preparation example can also be any one of titanium-aluminum alloy, nickel-titanium alloy, tungsten steel or chrome steel.

[0066] Comparative Preparation Example 1

[0067] The difference between this comparative preparation example and preparation example 1 is that no auxetic polymer and high hardness filler are used for cross-linking. The specific differences are as follows:

[0068] S2. The glass fiber is subjected to ultrasonic impurity removal treatment. After drying, 6g of the glass fiber is irradiated with ultraviolet light for 60 minutes, and then irradiated for 3 minutes under vacuum conditions using a YAMATO PR501-A low-temperature plasma treatment device with a radio frequency of 13.56MHz and an output power of 300W. The gas medium is one of N2. Ethanol is used as a dispersing solvent, and a lithium chloride anhydrous ethanol solution with a mass fraction of 6% is prepared. The treated glass fiber is immersed in the lithium chloride anhydrous ethanol solution, the temperature is raised to 70°C, the treatment time is 1.5h, and the activated glass fiber is obtained after washing with clean water and drying.

[0069] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0070] Comparative Preparation Example 2

[0071] The difference between this comparative preparation example and preparation example 1 is that no compound filler is used for mixing, but high hardness material is directly used for coupling modification. The specific differences are as follows:

[0072] S1. Take 20 g of aluminum-lithium alloy particles with a particle size of 50-70 μm, use a measuring cylinder to quantitatively prepare enough silane coupling agent KH560 with a mass fraction of 10%, and use ethanol as the solvent. Mix the above-prepared aluminum-lithium alloy and the prepared silane coupling agent, shake with an oscillator for 5 minutes, react for 1.5 hours, filter and dry to obtain a coupling filler.

[0073] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0074] Comparative Preparation Example 3

[0075] The difference between this comparative preparation example and preparation example 1 is that instead of using lithium chloride organic solution to disperse the flexibilizing polymer, sodium chloride organic solution is used for dispersion. The specific changes are as follows:

[0076] S2. The linear aromatic amide flexographic polymer obtained by the polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl ester and p-phenylenediamine is subjected to ultrasonic impurity removal treatment. After drying, 6 g of the flexographic polymer is irradiated with ultraviolet light for 60 minutes, and then irradiated for 3 minutes under vacuum conditions using a YAMATO PR501-A low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W. The gas medium is one of N2. Ethanol is used as a dispersing solvent, and a sodium chloride anhydrous ethanol solution with a mass fraction of 6% is prepared. The treated linear aromatic amide flexographic polymer is immersed in a lithium chloride anhydrous ethanol solution, the temperature is raised to 70°C, the treatment time is 1.5 hours, and the activated flexographic polymer is obtained after washing with clean water and drying.

[0077] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0078] Comparative Preparation Example 4

[0079] The difference between this comparative preparation example and preparation example 1 is that the dispersion medium used in step S3 is methanol, and the specific differences are as follows:

[0080] S3. Immerse the coupled composite filler in methanol, stir with an external stirrer to form a suspension, and adjust the pH to 10.0 with a sodium hydroxide solution with a concentration of 0.1 mol / L.

[0081] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0082] Comparative Preparation Example 5

[0083] The difference between this comparative preparation example and preparation example 1 is that the suspension of the coupled composite filler and the organic solution of the auxetic polymer are not subjected to alkaline and acid adjustment treatment. The specific differences are as follows:

[0084] S3, immersing the coupled composite filler in isopropanol and stirring with an external stirrer to form a suspension;

[0085] S4, dissolving the activated auxetic polymer material obtained in S2 in a dimethyl sulfoxide solution;

[0086] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0087] Comparative Preparation Example 6

[0088] The difference between this comparative example and Example 1 is that the auxetic polymer is not slowly added dropwise to the suspension of the coupled composite filler. The specific changes are as follows:

[0089] S5. Add the suspension of the coupled composite filler to the dimethyl sulfoxide solution containing the activated auxetic polymer by dropwise addition at a rate of 60 ml / min. React for 3 h, take out the modified auxetic molecules, wash them alternately with deionized water and ethanol, and dry them for later use.

[0090] The remaining steps are the same as those in Preparation Example 1 to obtain a modified filler.

[0091] Example 1

[0092] Preparation of a high-adhesion and wear-resistant metallic water-based coating

[0093] The filler used in this example is the modified auxetic molecule in Preparation Example 1.

[0094] 40 parts of water-based acrylic resin, 10 parts of filler, 16 parts of water, 9 parts of pigment, 0.3 parts of leveling agent, 0.3 parts of dispersant, 0.3 parts of mildew inhibitor, 0.2 parts of preservative, 0.2 parts of defoamer, 0.2 parts of wetting agent, 5 parts of isopropyl alcohol, 6 parts of propylene glycol butyl ether, and 8 parts of curing agent.

[0095] Mix deionized water with isopropyl alcohol and propylene glycol butyl ether for later use, add water-based acrylic resin, filler, pigment, leveling agent, dispersant, mildew inhibitor, preservative, defoamer and wetting agent into a container, stir evenly, and finally add a mixed solution of deionized water, isopropyl alcohol and propylene glycol butyl ether to form a viscous uniform fluid, and mix the curing agent with the uniform fluid before painting.

[0096] Example 2

[0097] Preparation of a high-adhesion and wear-resistant metallic water-based coating

[0098] The filler used in this example is the modified auxetic molecule in Preparation Example 1.

[0099] 50 parts of water-based acrylic resin, 15 parts of filler, 18 parts of water, 10 parts of pigment, 0.4 parts of leveling agent, 0.4 parts of dispersant, 0.4 parts of mildew inhibitor, 0.4 parts of preservative, 0.4 parts of defoamer, 0.4 parts of wetting agent, 6 parts of isopropyl alcohol, 8 parts of propylene glycol butyl ether, and 10 parts of curing agent.

[0100] Mix deionized water with isopropyl alcohol and propylene glycol butyl ether for later use, add water-based acrylic resin, filler, pigment, leveling agent, dispersant, mildew inhibitor, preservative, defoamer and wetting agent into a container, stir evenly, and finally add a mixed solution of deionized water, isopropyl alcohol and propylene glycol butyl ether to form a viscous uniform fluid, and mix the curing agent with the uniform fluid before painting.

[0101] Example 3

[0102] Preparation of a high-adhesion and wear-resistant metallic water-based coating

[0103] The filler used in this example is the modified auxetic molecule in Preparation Example 1.

[0104] 35 parts of water-based acrylic resin, 8 parts of filler, 14 parts of water, 8 parts of pigment, 0.2 parts of leveling agent, 0.2 parts of dispersant, 0.2 parts of mildew inhibitor, 0.2 parts of preservative, 0.1 parts of defoamer, 0.1 parts of wetting agent, 4 parts of isopropyl alcohol, 4 parts of propylene glycol butyl ether, and 5 parts of curing agent.

[0105] Mix deionized water with isopropyl alcohol and propylene glycol butyl ether for later use, add water-based acrylic resin, filler, pigment, leveling agent, dispersant, mildew inhibitor, preservative, defoamer and wetting agent into a container, stir evenly, and finally add a mixed solution of deionized water, isopropyl alcohol and propylene glycol butyl ether to form a viscous uniform fluid, and mix the curing agent with the uniform fluid before painting.

[0106] Comparative Example 1

[0107] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 1.

[0108] Comparative Example 2

[0109] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 2.

[0110] Comparative Example 3

[0111] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 3.

[0112] Comparative Example 4

[0113] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 4.

[0114] Comparative Example 5

[0115] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 5.

[0116] Comparative Example 6

[0117] The difference between this comparative example and Example 1 is that the filler used is the modified filler in Comparative Preparation Example 6.

[0118] Experiments and data

[0119] Coating method and parameters: The metallic water-based paint prepared in the above embodiment was applied with a coating thickness of 3 μm, 4 μm and 5 μm;

[0120] The coating is baked twice, the first baking temperature is 50°C, 65°C and 80°C, the time is 15 minutes, and the second baking temperature is 130°C, 150°C and 170°C, the time is 40 minutes, 30 minutes and 20 minutes.

[0121] The above coatings were subjected to performance tests, and the test standards were as follows:

[0122] The paint film adhesion test method is carried out in accordance with the standard GB9286-1998.

[0123] Testing standard: 0-100 / 100

[0124] The impact resistance test of paint film is carried out in accordance with the standard of GB / T1732-1993.

[0125] Testing standard: 50cm height impact test, surface cracks, wrinkles and peeling.

[0126] Friction and wear experiment, the specific steps are as follows:

[0127] After the paint is baked and fixed, the coating and the coating material are evenly rubbed on the paint film surface with water sandpaper, and the wear resistance is evaluated based on the adhesion on the sandpaper.

[0128] Testing standard: number of adhesions, weight dropped per 10g of paint.

[0129] The following table shows the test results of the coatings after the metallic water-based paints of Examples 1-3 and Comparative Examples 1-6 were applied.

[0130] Table 1

[0131]

[0132] Analysis Conclusion

[0133] According to the data in Table 1, the adhesion effect of the coating in Example 1, Example 2 and Example 3 of the present application is extremely strong, and the impact resistance performance has passed the test. Finally, the coating loss after friction with water sandpaper is small, the coating can be well retained, and will not be lost due to high-pressure friction, and has high wear resistance.

[0134] The adhesion of comparative example 1 is low and it fails the impact test. The amount of adhesion after friction is as high as 5.5g, which proves that the use of tensile polymer can effectively improve the resistance of high hardness fillers in the coating to impact and friction, effectively retain the resin molecules, and greatly improve the wear resistance of the coating.

[0135] The results of Comparative Example 2 show that the impact resistance is passed, but the adhesion is very poor, and the number of friction adhesions is the largest. It can be seen that the use of flaky graphite compounded with high-hardness fillers can effectively improve the mechanical locking between the modified tensile molecules and the resin in the coating, and plays a bridging role in the coating, performing interlocking connections between the molecules of the coating and enhancing the connection strength.

[0136] The results of Comparative Example 3 show that the adhesion is slightly poor, the impact resistance fails, and there are more adhesions after friction. The results show that the use of sodium chloride to pretreat the auxetic polymer material has little effect on destroying the hydrogen bonds between the auxetic polymer materials. Therefore, the connection between the coupled composite filler and the auxetic polymer only exists on the outside, and the auxetic properties of the auxetic polymer cannot be fully exerted. Therefore, the effect is similar to that of using ordinary fibers, and the rigidity of ordinary fibers is not strong, so the effect is worse.

[0137] In Comparative Example 4, methanol was used to disperse the coupled composite filler. The results showed good adhesion and impact resistance, proving that the connection between the flexographic polymer and the flaky graphite and the high-hardness filler was very good, and the mechanical properties were strong. However, there were many adhesions after friction, which showed that the active groups were consumed too much, and the coupling groups were not well cross-linked with the resin molecules in the subsequent process. It completely relied on the mechanical locking of the flaky graphite, so more of them fell off after friction.

[0138] The test results of Comparative Example 5 show that although the impact resistance test was passed, the adhesion was slightly poor and there were fewer friction adhesions. The results confirmed that the use of an alkaline environment to protect the coupled composite filler and the acidic environment to adjust the tensile polymer can effectively inhibit the activity of part of the coupling group and prevent the loss of activity. After mixing, the microenvironment is adjusted to neutral, which enhances the activity of the coupling group and can enhance the cross-linking effect in a complex environment.

[0139] The test results of Comparative Example 6 show that the adhesion is low, the impact resistance test fails, and there are many adherents. Combined with the addition order of Comparative Preparation Example 6, it can be seen that adding the suspension of the coupled composite filler to the organic solution of the flexographic polymer will completely consume the active groups of the coupled composite filler. The surface of each coupled composite filler particle is connected to multiple flexographic polymers. Therefore, when subjected to friction, the filler cannot effectively protect the flexographic polymer, and it is difficult to achieve the flexographic effect of the flexographic polymer.

[0140] Adding the flexibilizing polymer to the suspension of the coupled composite filler will cause more coupled composite filler particles to be connected to the molecular chain of the flexibilizing polymer, so that when subjected to friction, the flexibilizing polymer can better play its role and protect the paint coating.

[0141] The above is a preferred embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles described in the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.

Claims

1. A method for preparing a high-adhesion and wear-resistant metallic water-based coating, characterized in that: The filler used in the metallic waterborne coating is a modified auxetic molecule, and the preparation steps of the modified auxetic molecule are as follows: S1, mixing a high-hardness composite filler with a silane coupling agent, and performing a shaking treatment to obtain a coupled composite filler; S2, subjecting the flexibilized polymer to ultrasonic impurity removal treatment, drying and then irradiating with ultraviolet light, and then irradiating with YAMATOPR501-A type low-temperature plasma treatment device under vacuum conditions, with the gas medium being one of N2, H2 or NH3; Using ethanol as a dispersing solvent, preparing an anhydrous ethanol solution of lithium chloride, immersing the treated auxetic polymer in the anhydrous ethanol solution of lithium chloride, heating it, washing it with water and drying it, to obtain an activated auxetic polymer; S3, preparing a suspension of the coupled composite filler, using isopropanol as the dispersion medium, and adjusting the pH to alkaline; S4, dissolving the activated flexographic polymer in S2 in an organic solvent and adjusting the pH to acidic; S5, slowly dropping the organic solution of the auxetic polymer obtained in S4 into the suspension of the coupled composite filler obtained in S3, and adjusting the pH to neutral or slightly alkaline, wherein the mass ratio of the auxetic polymer to the coupled composite filler is 1:3-6; The auxetic polymer in S2 is a linear aromatic amide auxetic polymer, and the linear aromatic amide auxetic polymer is obtained by polycondensation reaction of 2,6-dichloroformyl tetraphenyl ethyl formate and p-phenylenediamine; The high-hardness composite filler is obtained by mixing a high-hardness material and flake graphite in a ratio of 1:1-3:1; The high-hardness material is one of tungsten carbide, aluminum-lithium alloy, titanium-aluminum alloy, nickel-titanium alloy, niobium-titanium alloy, tungsten steel or chrome steel.

2. The method for preparing a high-adhesion and wear-resistant metallic water-based coating according to claim 1, characterized in that: The metallic water-based paint comprises the following specific ingredients by weight: 35-50 parts of water-based acrylic resin, 8-15 parts of filler, 14-18 parts of water, 8-10 parts of pigment, 0.2-0.4 parts of leveling agent, 0.2-0.4 parts of dispersant, 0.2-0.4 parts of mildewproof agent, 0.2-0.4 parts of preservative, 0.1-0.4 parts of defoaming agent, 0.1-0.4 parts of wetting agent, 4-6 parts of isopropyl alcohol, 4-8 parts of propylene glycol butyl ether, and 5-12 parts of curing agent.

3. The method for preparing a high-adhesion and wear-resistant metallic water-based coating according to claim 1, characterized in that: The particle size of the high-hardness composite filler is between 30-100 μm.

4. The method for preparing a high-adhesion and wear-resistant metallic water-based coating according to claim 1, characterized in that: The organic solvent in S4 is one of dimethyl sulfoxide, N,N-dimethylformamide or ethylene glycol dimethyl ether.

5. A high-adhesion and wear-resistant metallic water-based paint, characterized in that: The metal water-based coating is prepared by the preparation method of any one of claims 1 to 4.

6. The high-adhesion and wear-resistant metallic water-based paint according to claim 5, characterized in that: The coating thickness of the metallic water-based paint is 3 to 5 μm; the coating is baked twice, the first baking temperature is 50 to 80° C., the time is 10 to 15 minutes, and the second baking temperature is 130 to 170° C., the time is 20 to 40 minutes.

7. Application of a high-adhesion and wear-resistant metallic water-based coating, characterized in that: The metallic water-based paint according to claim 6 is used for coating the surface of metal equipment.

Citation Information

Patent Citations

  • Preparation method and application of poly(4'''-ethyl formate)-p-quatelphenyl-2,6-diformyl p-phenylenediamine

    CN105524269A